The pre-teatment effect of voluntary exercise by GDNF on lesion injectioned by 6- hydroxydopamine in brain stem of male rats Abstract - راضیه محمدی; ضیاء فلاح محمدی; خدیجه آقاجانی; ابواقاسم تقوی هلق (Shahid Beheshti University, 2014)
Background&Purpose: The purpose of this research was to investigate the protective effect of voluntary exercise by GDNF on lesion induced by 6-hydroxydopamine in brainstem of male rats. Methods: In this study, 24 Wistar rats were randomly divided into four groups: healthy control, Parkinson-control, healthy- exercise, Parkinsonian group, that first exercised and then Parkinson was induced (Practice-treated). Subjects in exercise group were kept in special cages geared with running wheels for 12 weeks. After 12 weeks, 6- OHDA was injected into the right ventricle of the brain and five days after intraventricular injection, sampling was performed and GDNF level of brainstem was measured by ELISA method. Data were analyzed statistically by oneway ANOVA test and tukey post hoc. Results: The level of brain stem GDNF in parkinsonian-control have significantly decrease when compared with healthy training group (P-0.015). GDNF in parkinsonian-exercise have significantly increasewhen compared with parkinsonian-control (P-0.015).there are not significantly difference between healthy-exercise and parkinsonian-exercise with healthy-control respectively (P=0.87) and (P=0.95). difference between healthy-control and parkinsonian control was signifant (P-0.004). Conclusion: The findings of the present study show that pre-treatment with voluntary exercise can increase GDNF level of brain stem and can protect brainstem neurons against lesion by 6-OHDA toxicity.